2006
DOI: 10.1590/s1516-35982006000400022
|View full text |Cite
|
Sign up to set email alerts
|

Níveis de energia metabolizável mantendo a relação lisina digestível: caloria em rações para suínos machos castrados em terminação

Abstract: Metabolizable energy levels maintaining digestible lysine:calorie ratio in diets for finishing barrowsABSTRACT -Forty barrows from commercial hybrids averaging initial weight of 60.1 ± 1.3 kg were used in a trial to evaluate different ME levels, maintaining the digestible lysine:calorie ratio, on the performance and carcass characteristics. A randomized block experimental design with four treatments, five replicate and two animals per experimental unit was used. The treatments consisted of four ME levels (3,10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
8
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 11 publications
4
8
1
5
Order By: Relevance
“…These data confirm the studies conducted by Rezende et al (2006), who also have observed no effect of the dietary levels of ME on this variable in animals from 60 to 95 kg.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…These data confirm the studies conducted by Rezende et al (2006), who also have observed no effect of the dietary levels of ME on this variable in animals from 60 to 95 kg.…”
Section: Resultssupporting
confidence: 92%
“…Since no differences were observed (P>0.05) in ME intake, these data are consistent with those obtained by Trindade Neto et al (2005), who when assessing growing pigs between 23 and 48 kg of body weight have found that these animals can transform their feed intake into energy intake. These results are similar to the ones obtained by Rezende et al (2006), who have observed a reduction in the ADFI due to the increase in the energy density of diets for growing pigs (60 to 95 kg). Similarly, Santos et al (2005), when evaluating gilts fed three levels of total lysine (0.55, 0.75 and 0.95%) and three levels of ME (3100, 3250 and 3400 kcal/kg) with a content of 13% crude protein (CP) have also observed a reduction in ADFI with an increase in the content of ME.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Esse resultado é corroborado pelos Tabela 2 -Desempenho de leitoas em terminação, sob estresse por calor, alimentadas com dietas contendo níveis de energia líquida (EL) e suplementadas com ractopamina (Rac). Estas variações do CRD podem estar relacionadas aos ajustes da demanda energética dos animais, de forma que a baixa densidade energética das dietas é compensada com o aumento do consumo até que determinado nível de exigência de energia seja atingido (REZENDE et al, 2006). Provavelmente, no presente estudo, esta resposta não foi constatada, uma vez que os animais foram submetidos a temperaturas ambientais elevadas que podem ter deprimido a ingestão voluntária de alimento.…”
Section: Resultsunclassified